PSYCHOLOGICAL CONDITIONS OF STUDENTS IN THE IMPLEMENTATION OF LEARNING DURING THE COVID-19 PANDEMIC - Hasanah, Roudatul; Maulidi, Achmad (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
This research is a research that uses a qualitative approach with a case study research design. This study uses data collection techniques through observation, interviews, and documentation. The focus of the problem in this study is (1) how is the psychological condition of students in implementing learning during the COVID-19 pandemic and (2) what are the obstacles and solutions that students experience when participating in the learning process during the COVID-19 pandemic. This study has a purpose, namely (1) to find out how the psychological condition of students when participating in the learning process during the Covid-19 pandemic and (2) to find out what obstacles and solutions students experience when participating in the learning process during the Covid-19 pandemic. The data and data sources in this study are written narratives in the form of information from students, teachers, and guardians. This study uses data analysis from the Miles and Huberman model which is carried out through three steps, namely (1) Data Reduction (2) Data Presentation, and (3) Data Verification. The result of this study indicates that the psychological condition of students in implementing learning is that students stress when participating in learning and are too lazy to study due to a lack of motivation. Obstacles and solutions experienced by students in implementing learning during the pandemic (1) facilities that are less supportive and (2) difficulties in understanding lessons.